POLITIK LINGKUNGAN GLOBAL DALAM PRAKTIK PENEBANGAN LIAR DI INDONESIA (STUDI KASUS: PERAN PEMERINTAH & UNFF) - Amsir, Achmad Abdi; Dwi Rezeki, Kurniawan (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2026)
Illegal logging constitutes one of the most pressing global environmental challenges, with severe consequences for ecosystem integrity and accelerating climate change. Indonesia, endowed with one of the world’s largest tropical forest estates, confronts substantial governance challenges in suppressing this illicit practice. This study investigates the roles of the Indonesian government and the United Nations Forum on Forests (UNFF) in addressing illegal logging, employing Green Politics theory to assess the ecological sustainability orientation of Indonesia’s forest policies and Global Governance theory to evaluate UNFF’s contribution as a multilateral actor in shaping international forestry norms. The findings reveal that, despite the implementation of significant policy instruments—including the forest concession moratorium (Presidential Instruction No. 10/2011) and the Timber Legality Verification System (SVLK)—their effectiveness remains circumscribed by persistent weaknesses in law enforcement, entrenched corruption, and competing economic interests. Concurrently, UNFF contributes a global normative framework through its Non-Legally Binding Instrument (NLBI) on Sustainable Forest Management, facilitating international cooperation and technical assistance, including satellite-based forest monitoring technology transfers to Indonesia. However, the non-binding nature of UNFF’s instruments constitutes a structural limitation, reducing its capacity to compel meaningful behavioral change among member states. This study underscores the imperative of strengthened multi-stakeholder collaboration—encompassing governments, international organizations, and local communities—to overcome these governance deficits and advance effective, sustainable forest management.